2020
DOI: 10.1111/apt.16097
|View full text |Cite
|
Sign up to set email alerts
|

East Asia expert opinion on treatment initiation for chronic hepatitis B

Abstract: Background: Globally, chronic hepatitis B (CHB) is a major public health concern. Timely and effective management can prevent disease progression to cirrhosis and reduce the risk of hepatocellular carcinoma (HCC). Currently, there is no consensus on the clinical management of CHB in East Asia. Aim: To establish an East Asia expert opinion on treatment initiation for CHB based on alanine aminotransferase (ALT) level, hepatitis B virus (HBV) deoxyribonucleic acid (DNA) level, cirrhosis and HCC risk scores. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 50 publications
(113 reference statements)
2
63
0
Order By: Relevance
“…Indeed, subsequent data from the same cohort showed that patients with HBV DNA levels of >10 7 copies/ml had a significantly lower risk of HCC than those with HBV DNA levels between 10 6 and 10 7 copies/ml. 23,43,44 In accordance, in our recent historical cohort study including 6949 non-cirrhotic patients without significant ALT elevation (<2 × ULN at least for 1 year) regardless of HBeAg positivity, the association between HBV DNA levels and HCC risk was not linear but parabolic, showing the highest HCC risk with moderate serum HBV DNA levels of 5.0-7.0 log 10 IU/ml and lowest HCC risk with HBV DNA level of >8 log 10 IU/ml and ≤4 log 10 IU/ml, regardless of ALT levels. 32 A recently published multicenter historical cohort study also confirmed a low risk of HCC development in untreated non-cirrhotic patients with HBV DNA level >10 7 IU/ml.…”
Section: Serum Hbv Dna Levels and The Risk Of Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, subsequent data from the same cohort showed that patients with HBV DNA levels of >10 7 copies/ml had a significantly lower risk of HCC than those with HBV DNA levels between 10 6 and 10 7 copies/ml. 23,43,44 In accordance, in our recent historical cohort study including 6949 non-cirrhotic patients without significant ALT elevation (<2 × ULN at least for 1 year) regardless of HBeAg positivity, the association between HBV DNA levels and HCC risk was not linear but parabolic, showing the highest HCC risk with moderate serum HBV DNA levels of 5.0-7.0 log 10 IU/ml and lowest HCC risk with HBV DNA level of >8 log 10 IU/ml and ≤4 log 10 IU/ml, regardless of ALT levels. 32 A recently published multicenter historical cohort study also confirmed a low risk of HCC development in untreated non-cirrhotic patients with HBV DNA level >10 7 IU/ml.…”
Section: Serum Hbv Dna Levels and The Risk Of Hccmentioning
confidence: 99%
“…45 According to these results, traditional paradigm of "linear association" between HBV DNA and the risk of HCC may have to be revised to "parabolic association." 44 Serum HBV DNA levels may be changed by interaction between the host and virus during the natural course of CHB. Most of the patients with CHB have very high levels (≥8 log 10 IU/ml) of HBV DNA at the initial phase of the infection.…”
Section: Serum Hbv Dna Levels and The Risk Of Hccmentioning
confidence: 99%
“…The recent East Asia Consensus 1 and official guideline 2 on treatment initiation for chronic hepatitis B recommend that indications for anti‐viral therapies are mainly related to four factors, namely hepatitis B virus (HBV) deoxyribonucleic acid (DNA), alanine aminotransferase (ALT), cirrhosis, and family history of hepatocellular carcinoma (HCC). Aspartate aminotransferase (AST) is not considered a necessary factor in treatment decision.…”
Section: Figurementioning
confidence: 99%
“…We thank Li and colleagues for their letter 1 commenting on our recent expert opinion paper 2 and sharing their observations. They highlighted the potential role of elevated serum aspartate aminotransferase (AST) level in predicting the overall survival of patients who had undergone liver resection for hepatocellular carcinoma, mostly due to chronic hepatitis B.…”
mentioning
confidence: 98%
“…A number of generic fibrosis scores such as the AST‐to‐alanine aminotransferase (ALT) ratio, AST‐to‐platelet ratio index (APRI) and the Fibrosis‐4 index include AST as an integral component 3 . In our paper, we recommended the use of APRI and Fibrosis‐4 index to evaluate for significant liver fibrosis and cirrhosis, especially in resource‐limited areas 2 . However, clinicians should exercise caution when interpreting these scores in patients with normal ALT levels and in those on antiviral treatment as false‐negative results are common 4 .…”
mentioning
confidence: 99%